Synthesis and characterization of palm oil based surfactant by chemical transesterification / Sanaz Shahla - Sanaz, Shahla (2014)
Surfactants are a class of chemical products that have wide applications. The existing commercial surfactants extensively used in the cleaning agents and health care products are produced from petrochemical resources. Besides the limitation of the petrochemical resources and low degradability of the petrochemical-based synthesized surfactants, their toxicity and allergenic side effects on the human health need to be seriously considered which has thus prompted the use of oleochemicals such as palm oil to replace petrochemicals as natural raw material in the surfactants production. In this work, synthesis of palm oil based surfactants was investigated. The reaction of palm oil ethyl esters with polyethylene glycol 600 was selected as a possible approach for synthesis of surfactants. Transesterification of palm oil with ethanol which is also known as ethanolysis was the basic reaction for the production of palm oil ethyl esters. The optimization and kinetic studies were first conducted on chemical ethanolysis of palm oil. Major parameters including the reaction temperature, molar ratio of the reactants and catalyst concentration were determined by means of design of experiments and response surface methodology through the optimization study. The study showed a reduced cubic model with excellent conformity between the actual values of conversion and the predicted amounts of palm oil ethyl ester conversion. Numerical optimization studies on the reaction showed that high ethyl ester conversions are achievable by minimizing the ethanol usage and reaction temperature, while maximizing the concentration of the alkaline catalyst. A reaction temperature of 25˚C, 12:1 molar ratio of ethanol:oil and 1.25 wt% of sodium ethoxide were found as the optimum conditions to obtain close to 100% ethyl ester conversion. The catalyst concentration was found to be the most influencing factor for the ethanolysis conversion. Investigation of various kinetic models indicated that palm oil ethanolysis reaction fitted well to an irreversible second order kinetic model with a minimum of 92% level of confidence. The rate constants and activation energy of the reaction were calculated as 0.018 dm3/mol.min ‒ 0.088 dm3/mol.min and 42.36 KJ/mol, respectively. In the production of surfactant, preliminary studies showed that surface active agents could be successfully synthesized using 1:1 to 4:1 molar ratios of PEG to palm oil ethyl esters and 1 wt% alkaline catalyst at 60˚C. The quantitative study of the reaction using HPLC equipped with UV detector showed that mono- and di-polyethylene glycol ethyl esters were the main products that were produced through a series of reactions. The study also showed fast decrease in the concentration of the reactants in the first minutes of the reactions. Furthermore, increasing the molar ratio of PEG 600 to palm oil ethyl esters up to 4:1 eliminates the reverse production of ethyl esters through the reaction. The characterization study of the synthesized surfactants showed that they possessed comparable surface tension, foaming and emulsifying properties with those of the commercial surfactants.